The Legal Status of the Financial Action Task Force in the International Legal System - Ferreira, Ilda Cristina, (International and Comparative Business Law and Public Policy ;, 2025)
The FATF challenges traditional axioms and patently illustrates the dynamics of the international legal system. This book fills a significant gap in academic literature by studying FATF's legal nature and its responsibilities in the international legal system as an organisation with public authority. It makes a bold argument that the FATF has gradually evolved into an international organisation, addressing international law and international organisation law discourse, combining theory and practice. This book's analytical framework can be applied to any organisation whose legal nature remains undefined, attempting to provide clarity and legal certainty in the international legal system's architecture of the 21st century.